Differences in motor network dynamics during recovery between supra‐ and infra‐tentorial ischemic strokes - Lee, Jungsoo (Hum Brain Mapp, 2018)
Most previous stroke studies have been performed in heterogeneous patient populations. Moreover, the brain network might demonstrate different recovery dynamics according to lesion location. In this study, we investigated variation in motor network alterations according to lesion location. Forty patients with subcortical ischemic stroke were enrolled. Patients were divided into two groups: 21 patients with supratentorial stroke (STS) and 19 patients with infratentorial stroke (ITS). All patients underwent resting‐state functional magnetic resonance imaging and behavioral assessment at 2 weeks and 3 months poststroke. Twenty‐four healthy subjects participated as a control group. To compare altered connectivity between groups, measures used in previous studies to evaluate interhemispheric balance and global network reorganization were investigated and the relationship between network measures and motor functions were examined. Cortico‐cerebellar connectivity was also extracted to investigate its relationship with interhemispheric connectivity. In the STS group, measures related to interhemispheric balance were disrupted compared to the control group 2 weeks poststroke, while this was not found in the ITS group. During recovery, measures related to global network reorganization in the STS group and measures related to interhemispheric balance in the ITS group demonstrated significant changes, respectively. Moreover, motor functions were correlated with altered network measures in both groups. There was an interactive relationship between cortico‐cerebellar and interhemispheric cortical connectivity only in the ITS group. Different changes in the motor network were observed depending on the location of stroke lesions. These results might originate from differences in the interactions between cortico‐cerebellar and interhemispheric connectivity.